Creld1 regulates myocardial development and function. (July 2021) - Beckert, Vera; Rassmann, Sebastian; Kayvanjoo, Amir Hossein; Klausen, Christina; Bonaguro, Lorenzo; Botermann, Dominik Simon; Krause, Melanie; Moreth, Kristin; Spielmann, Nadine; da Silva-Buttkus, Patricia; Fuchs, Helmut; Gailus-Durner, Valerie; et al.
Abstract: CRELD1 (Cysteine-Rich with EGF-Like Domains 1) is a risk gene for non-syndromic atrioventricular septal defects in human patients. In a mouse model, Creld1 has been shown to be essential for heart development, particularly in septum and valve formation. However, due to the embryonic lethality of global Creld1 knockout (KO) mice, its cell type-specific function during peri- and postnatal stages remains unknown. Here, we generated conditional Creld1 KO mice lacking Creld1 either in the endocardium (KO Tie2 ) or the myocardium (KO MyHC ). Using a combination of cardiac phenotyping, histology, immunohistochemistry, RNA-sequencing, and flow cytometry, we demonstrate that Creld1 function in the endocardium is dispensable for heart development. Lack of myocardial Creld1 causes extracellular matrix remodeling and trabeculation defects by modulation of the Notch1 signaling pathway. Hence, KO MyHC mice die early postnatally due to myocardial hypoplasia. Our results reveal that Creld1 not only controls the formation of septa and valves at an early stage during heart development, but also cardiac maturation and function at a later stage. These findings underline the central role of Creld1 in mammalian heart development and function. Graphical abstract: Unlabelled Image Highlights: Creld1 controls cardiac maturation and function. Creld1 function is essential in the myocardium, but rather dispensable in the endocardium. Loss of myocardial Creld1 causes extracellular matrix remodeling and myocardial hypoplasia, leading to neonatal death.